Fotoproteksi Kurkumin terhadap β-Karoten pada Berbagai Nisbah Molar serta Aktivitas Antioksidannya - Natalina, Elly; Rahayu, Puji; Sulistyowati, Sulistyowati; Limantara, Leenawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Curcumin and β-carotene are two kinds of pigments serve as antitumor, anticancer and antioxidant agents. Theantioxidant activity of curcumin is stronger and more stable as compared to β-carotene, so it can protect β-carotene degradation from light and oxygen. Therefore curcumin has higher antioxidant activity as well. Theresearch was conducted by mixing curcumin and β-carotene in several molarity ratios followed by iradiation usingvolpi lamp for 0, 10, 30, 60, and 90 minutes. The result shows that curcumin has photoprotection effect because itcan protect photooxidation of β-carotene. Mixing of curcumin and β-carotene 1:1 was the most stable ratio forprotecting β-carotene.